Utopías, desencantos y esperanzas en la construcción de una comunidad imaginada. Waslala memorial del futuro de Gioconda Belli - Fernández Carballo, Rodolfo (2006)
The present article recounts to the link and process of construction of the statement of the utopia in the work Waslala Memorial del futuro, and the historical-social conjuncture in which one finds the enunciation subject inmersed while being transindividual and collective subject. The implicit theoretical perspective points at the study of the relations between the utopian statement and the social-historical contexts where they take place, starting off from the Bakhtinians theoretical principles that establish a narrow link between the text and the society, and  the enunciation and the social valuation. As far as the utopia concept, it is understood as an idea that tries to achieve the correction of the reality by means of a proposal of having to be, utopia that imagines a happy space and that in so much artistic-literary production, it refracts the aspiration of a society that criticizes the existing order, and  proposes the one that must be.